INCLINATION ANALYSIS OF STUDENT CAPABILITIES IN PROMISED TEACHERS OF THE LEARNING INDEPENDENCE PERSPECTIVE: EXPLORATION STUDY - Hidayati, Siti Nurul; Subekti, Hasan; Dasna, I Wayan; Wonorahardjo, Surjani; Munzil, Munzil; Nurkholis, Nurkholis (Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
Capabilities include competence, self-efficacy; self-confidence; self-discipline; to be responsible; self-initiative; and metacognition and what someone will bring to the workforce. This research strives to analyze the capability preferences of the prospective teacher in terms of learning independence. This descriptive study uses learning methods. Participants in this research were 21 students from the State University in East Java using purposive sampling techniques. The probing question is used as a research instrument. Descriptive data analysis. The consequences of data analysis explained that the ability in the aspect of high score learning skills was 85.4% responsible, 84.1% confidence, and 82.5% self-discipline. The conclusion of this study is the efficacy of the prospective student teacher from the perspective of independence learning shows the quality in the aspects of responsibility, self-confidence, and self-discipline. Nevertheless, the representative of self-establishment shows a lower trend correlated to other guidelines as much as 79.5%, or in other words, the meaning of participants is not optimum concerning their own desire for independence. This study reserves the need for further investigation into efforts to enhance the ability of prospective student teachers in higher education in theoretical and practical examinations.Keywords:Â Capabilities, Exploration, Learning independence, Promised teachers